Adsorption of Dissociating Aromatic Compounds by Activated Carbon: Effects of Ionization on the Adsorption Capacity - S. Nouri; Fouad Haghseresht (Adsorption Science & Technology)
The adsorption of three dissociating aromatic compounds on an untreated commercially available activated carbon was investigated systematically. All adsorption experiments were carried out in pH-controlled aqueous solutions. The experimental isotherms were analyzed using the homogeneous Langmuir model. The effects of surface heterogeneity were investigated via the theory of localized physical adsorption, using the Langmuir equation as the local isotherm equation and assuming a Gaussian adsorption energy distribution. A new method of utilizing the extracted parameters from the homogeneous and heterogeneous models is presented. This new approach provided a better understanding of the change in monolayer capacity and other adsorption characteristics of a carbon/solute system with pH.